Inter-disciplinarité et trans-nationalisme - Anne-Hélène Miller (Perspectives Médiévales)
This article examines the state of research and teaching of medieval French in the current context of the transnational approaches that influence interdisciplinary programs in medieval studies in North America. Often impacted by the research in postcolonial medievalism or medieval multiculturalism, (such as the programs that focus on the Mediterranean or francophone spaces in the Middle Ages), and liberated from nationally affiliated identities, today's scholars rethink territorial, linguistic, religious, even periodical delimitations, to decenter the more traditional discourse on the Medieval Latin West. We consider how, especially from a theoretical standpoint, Medieval French Studies have contributed and continue to impact this approach. We also confront some of the challenges to French Medieval Studies caused by these new directions in academia.